A numerical investigation of a wind turbine wake in non-neutral atmospheric conditions. Issue 2 (1st May 2022) - Baungaard, M.; Abkar, M.; van der Laan, M.P.; Kelly, M.
Abstract: Wind turbine wakes cause energy losses and increased blade fatigue loads in wind farms. The magnitude of these effects depend strongly on the atmospheric conditions. In nonneutral atmospheric conditions, there is a turbulence kinetic energy (TKE) contribution from buoyancy, either positive (convective boundary layer, CBL) or negative (stable boundary layer, SBL). In this work, both conditions are analyzed with new large-eddy simulation (LES) data of a single wind turbine wake in flat, homogeneous terrain to quantify the effects of buoyancy. It is found that the buoyancy contribution is negligible compared to the shear production in the wake region and the role of buoyancy is therefore mainly to alter the inflow profiles. This fact is used in a simple Reynolds-averaged Navier-Stokes (RANS) turbulence model, which shows reasonable results for wake velocity deficit compared to LES data.